SLC1A4 mutations cause a novel disorder of intellectual disability, progressive microcephaly, spasticity and thin corpus callosum. (28th July 2015) - Heimer, G.; Marek‐Yagel, D.; Eyal, E.; Barel, O.; Oz Levi, D.; Hoffmann, C.; Ruzzo, E.K.; Ganelin‐Cohen, E.; Lancet, D.; Pras, E.; Rechavi, G.; Nissenkorn, A.; et al.
<x xml:space="preserve">Abstract</x> Two unrelated patients, presenting with significant global developmental delay, severe progressive microcephaly, seizures, spasticity and thin corpus callosum (CC) underwent trio whole‐exome sequencing. No candidate variant was found in any known genes related to the phenotype. However, crossing the data of the patients illustrated that they both manifested pathogenic variants in the SLC1A4 gene which codes the ASCT1 transporter of serine and other neutral amino acids. The Ashkenazi patient is homozygous for a deleterious missense c.766G>A, p.(E256K) mutation whereas the Ashkenazi‐Iraqi patient is compound heterozygous for this mutation and a nonsense c.945delTT, p.(Leu315Hisfs*42) mutation. Structural prediction demonstrates truncation of significant portion of the protein by the nonsense mutation and speculates functional disruption by the missense mutation. Both mutations are extremely rare in general population databases, however, the missense mutation was found in heterozygous mode in 1:100 Jewish Ashkenazi controls suggesting a higher carrier rate among Ashkenazi Jews. We conclude that SLC1A4 is the disease causing gene of a novel neurologic disorder manifesting with significant intellectual disability, severe postnatal microcephaly, spasticity and thin CC. The role of SLC1A4 in the serine transport from astrocytes to neurons suggests a possible pathomechanism for this disease and implies a potential therapeutic approach.